UTILIZATION OF DIGITAL MARKETING IN INCREASING SALES OF MSME IN BENGKALIS REGENCY (Case Study on MSME of MARTABAK MANDOR, Gatot Subroto Street, Bengkalis City - Piani, Jus (Politeknik Negeri Bengkalis, 2024)
This research project aims to utilize digital marketing to increase sales of Msme Martabak Mandor Gatot Subroto Street, Bengkalis City. ImplementationThis project is carried out through 3 stages, namely (1) project preparation planning, (2) project implementation planning, and third (3) project completion stage. the form of digital marketing used is E-mail marketing and Social Media Marketing.The results of the application of digital marketing in Msme Martabak Mandor have increased sales revenue by 27.9%.This also proves that the application of digital marketing is able to increase sales of Msme Martabak Mandor. Consumers are interested in ordering online and there are also consumers who make direct purchases and repeat purchases.Keywords: Digital Marketing, MSME, E-mail Marketing, Social Media Marketing